ISLAMIC COMMUNICATION IN TOURISM: MUSLIM IDENTITY AND ISLAMIC PUBLIC SPHERE AT PUNCAK WAKILA, INDONESIA - Muhammad Obie (Universitas Islam Negeri Mataram, 2026)
Studies of Islamic communication today have predominantly focused on issues of authority, media, and da‘wah, while scholarly attention to Islamic communication within public spaces remains limited, including tourism sites as spaces that reveal Muslim interaction and identity. This study employs a qualitative method based on visual observation and documentation of social activities taking place in the tourism area. The findings show that Puncak Wakila functions as an informal Islamic public sphere characterized by collective social interaction, visible expressions of Muslim identity, and communication practices embedded in everyday public life. This tourism area serves not only as a recreational destination but also as a social space in which religious identity gains meaning through public interaction and participation.